Perceived quality of surgical care in association with patient-related factors and correlation to reported postoperative complications in Finland: a cross-sectional study - Helena Saarinen; Jaana-Maija Koivisto; Antti Kaipia; Elina Haavisto (BMJ PUBLISHING GROUP, 2022)
Objective To study if patient-related factors are associated with patient-evaluated quality of care in surgery. To examine if there is an association with postoperative complications and patient-evaluated low quality of care.
Design A correlation cross-sectional study, in addition, a phone call interview at 30 days postoperatively to examine complications.
Setting The data on patients admitted for non-cardiac general and orthopaedic surgery at a central hospital in Southwestern Finland were collected in two phases during an 8-month period.
Participants 436 consecutive consenting and eligible in-ward non-cardiac general surgery and orthopaedic surgery adult patients. Ambulatory, paediatric and memory disorder patients were excluded. 378 patients completed the questionnaire (Good Nursing Care Scale for Patients (GNCS-P)).
Methods Perceived quality of care was examined by the GNCS-P questionnaire. Patient-related factors were obtained from electronic patient records and questionnaire. A telephone interview related to postdischarge complications was conducted 30 days after discharge.
Main outcome measures Patient evaluation of quality of care at discharge, its association with patient-related factors and patient-reported postdischarge complications.
Results The overall quality was evaluated high or very high by the patients. The lowest overall quality of care rate was assessed by surgical patients living alone (p=0.0088) and patients who evaluated their state of health moderate or poor (p=0.0047). Surgical patients reporting postoperative complications after discharge evaluated lower overall quality of care (p=0.0105) than patients with no complications.
Conclusion Patient demographic factors do not seem to influence the perceptions of the quality of care. Instead, subjective state of health and living conditions (living alone) may have an influence on the patient experience of quality of care. The perceived quality of care in healthcare staff technical and communication skills may have an association with reported postoperative complications.